Exploring the Association between Procedural Justice in Jails and Incarcerated People's Commitment to Institutional Rules. Issue 3 (27th May 2021) - Baker, Thomas; Abderhalden, Frances P.; Alward, Lucas M.; Bedard, Laura E.
ABSTRACT: The process-based model of self-regulation has been evaluated throughout various agencies of the criminal justice system. However, the model has yet to be tested within jails. The goal of the current study is to fill this gap in the literature. Using a sample of 290 men and women incarcerated in a county jail, this study examines the association between inmates' procedural justice perceptions of detention officers and their commitment to institutional rules. Results suggest that net of demographic factors, prior misconduct, and a set release date, procedural justice is the strongest predictor of self-regulation in jails. Policy implications and suggestions for future research are discussed.